Speeding Up the Heart? Traditional and New Perspectives on HCN4 Function - Hennis, Konstantin; Rötzer, René D.; Piantoni, Chiara; Biel, Martin; Wahl-Schott, Christian; Fenske, Stefanie (Frontiers in Physiology, 2021)
The sinoatrial node is the primary pacemaker of the heart and is responsible for generating the intrinsic heartbeat. Within the sinoatrial node, spontaneously active pacemaker cells initiate the electrical activity that causes the contraction of all cardiomyocytes. The firing rate of pacemaker cells depends on the slow diastolic depolarization and determines the intrinsic heart rate. To adapt cardiac output to varying physical demands, heart rate is regulated by the autonomic nervous system. The sympathetic and parasympathetic branches of the autonomic nervous system innervate the sinoatrial node and regulate the firing rate of pacemaker cells by accelerating or decelerating slow diastolic depolarization–a process well-known as the chronotropic effect. Although this process is of fundamental physiological relevance, it is still incompletely understood how it is mediated at the subcellular level. Over the past 20 years, most of the work to resolve the underlying cellular mechanisms has made use of genetically engineered mouse models. In this review, we focus on the findings from these mouse studies regarding the cellular mechanisms involved in the generation and regulation of the heartbeat, with particular focus on the highly debated role of the hyperpolarization-activated cyclic-nucleotide gated cation channel HCN4 in mediating the chronotropic effect. By focusing on experimental data obtained in mice and humans, but not in other species, we outline how findings obtained in mice relate to human physiology and pathophysiology and provide specific information on how dysfunction or loss of HCN4 channels leads to human sinoatrial node disease.